Religious Commodification: Muslim Housing and Identity Affirmation in Lombok, Indonesia - Suprapto, Suprapto; Huda, Miftahul (Studia Islamika, 2023)
The rise of Muslim housing in Lombok excites the question of whether it indicates people’s religiosity reinforcement or religious symbol exploitation in business. Exclusive residences for a particular religious community may seed spatial and social segregation. Religiously separated houses may threaten social integration. This article is based on field research focusing on Muslim housing developers’ motives, consumers’ reasons, and the dynamic interaction of Muslim housing residents and its impact on social integration. This study shows that religious commodification in the property business allures consumers, particularly urban Muslims. Religious commodification also affirms Islamic identity but does not contribute to the piety enhancement of Muslim housing residents. Furthermore, Muslim housing development does not disrupt social interaction and cooperation among people in a multicultural society. Exclusivism and religious extremism are not troublesome. However, the potential of sporadic Islamic sectarianism to a comparatively small degree in some Muslim residential complexes should be taken into consideration.